1997
DOI: 10.1103/physreve.56.2924
|View full text |Cite
|
Sign up to set email alerts
|

Bjerknes forces between small cavitation bubbles in a strong acoustic field

Abstract: The mutual interaction between small oscillating cavitation bubbles (R 0 Ͻ10 m) in a strong acoustic field ͑P a Ͼ1 bar, f ϭ20 kHz͒ is investigated numerically. We assume spherical symmetry and a coupling of the bubble oscillations. Our results show that the strength and even the directions of the resulting secondary Bjerknes forces differ considerably from predictions of the well-known linear theory. This is of immediate consequence for understanding and modeling structure formation processes in acoustic cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
335
0
9

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(357 citation statements)
references
References 14 publications
13
335
0
9
Order By: Relevance
“…Interactions between bubbles and their emitted sound fields will be very important above a certain volume fraction of gas, which may be as low as 10 Ϫ5 (Marsh et al, 1998). These interactions take on a plethora of different shapes, such as secondary Bjerknes forces (Brennen, 1995;Mettin et al, 1997), bubble shadowing (Marsh et al, 1998), collective bubble collapses (Brennen, 1995), or collective bubble translation (streamers; Akhatov et al, 1996). In addition, multibubble applications always have to deal with the interaction of bubbles with boundaries, be they hard (as in materials science) or soft (as in biological and medical contexts).…”
Section: E Multibubble Fields: In Search Of a Theorymentioning
confidence: 99%
“…Interactions between bubbles and their emitted sound fields will be very important above a certain volume fraction of gas, which may be as low as 10 Ϫ5 (Marsh et al, 1998). These interactions take on a plethora of different shapes, such as secondary Bjerknes forces (Brennen, 1995;Mettin et al, 1997), bubble shadowing (Marsh et al, 1998), collective bubble collapses (Brennen, 1995), or collective bubble translation (streamers; Akhatov et al, 1996). In addition, multibubble applications always have to deal with the interaction of bubbles with boundaries, be they hard (as in materials science) or soft (as in biological and medical contexts).…”
Section: E Multibubble Fields: In Search Of a Theorymentioning
confidence: 99%
“…Comparison of this destruction of the foil with the distribution of the VDPCE shows that the model is applicable even in the presence of several independent waves in the liquid, if the oscillations are the coherent. By phenomenological description of this model can explain fact of the dependence of pressure, achieved on collapse of a bubble from the size of the all cavitation field which is established, for example, in [16,38]. The parameters N or D, R 0 and P* -the constants, that characterize a specific liquid and its behavior in cavitation process.…”
Section: Discussion Of Results Of the Computational Experiments Withmentioning
confidence: 99%
“…Acoustic cavitation it is ripple of the vapor-gas bubbles which concentrated under the action of the ponderomotive and hydrodynamic forces in the so-called cavitation areas near antinodes of sound pressure, where it amplitude in elastic wave in the liquid exceeds a certain threshold [1,2,3]. They produce the cavitation noise (the secondary sound).…”
Section: Introductionmentioning
confidence: 99%
“…32 It is found that the coupling of bubbles may lead to a variety of phenomena that a single bubble can never exhibit, such as attraction and repulsion of pulsating bubbles, 24,28,33,34 phase delays 35 and even coalescence. 36,37 However, most previous studies on BBI in these flow fields focused on the oscillations of bubbles at their static balance positions, which denote the positions of stationary bubbles when the inner pressure equals to the fluid pressure outside, instead of the translations of bubbles, so the effect of BBI on the motion equations of moving bubbles has been seldom considered.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, BBI have been extensively studied in various flow fields, such as in infinite flow field, 22,23 near the walls, [24][25][26] in homogeneous bubbly flows, 27 in a sound field [28][29][30][31] and under given pressure waves. 32 It is found that the coupling of bubbles may lead to a variety of phenomena that a single bubble can never exhibit, such as attraction and repulsion of pulsating bubbles, 24,28,33,34 phase delays 35 and even coalescence.…”
Section: Introductionmentioning
confidence: 99%